Interpreting violence : narrative, ethics and hermeneutics - Falke, Cassandra, 1977-; Fareld, Victoria, 1973-; Meretoja, Hanna, 1977- (New York, NY : Routledge, 2023)
"Representations of violence surround us in everyday life - in news reports, films and novels - inviting interpretation and raising questions about the ethics of viewing or reading about harm done to others. How can we understand the processes of meaning-making involved in interpreting violent events and experiences? And can these acts of interpretation themselves be violent by reproducing the violence that they represent? This book examines the ethics of engaging with violent stories from a broad hermeneutic perspective. It offers multidisciplinary perspectives on the sense-making involved in interpreting violence in its various forms, from blatant physical violence to less visible forms that may inhere in words or in the social and political order of our societies. By focusing on different ways of narrating violence and on the cultural and paradigmatic forms that govern such narrations, Interpreting Violence explores the ethical potential of literature, art and philosophy to expose mechanisms of violence while also recognizing their implication in structures that contribute to or benefit from practices of violence"--
Keywords: Violence in literature; Violence in popular culture